Power output during a professional men's road-cycling tour - Ebert, T. R.; Martin, D. T.; Stephens, B.; Withers, R. T. (International Journal of Sports Physiology and Performance, 2006)
To quantify the power-output demands of men's road-cycling stage racing using a direct measure of power output. Methods: Power-output data were collected from 207 races over 6 competition years on 31 Australian national male road cyclists. Subjects performed a maximal graded exercise test in the laboratory to determine maximum aerobic-power output, and bicycles were fitted with SRM power meters. Races were described as flat, hilly, or criterium, and linear mixed modeling was used to compare the races. Results: Criterium was the shortest race and displayed the highest mean power output (criterium 262 ± 30 v hilly 203 ± 32 v flat 188 ± 30 W), percentage total race time above 7.5 W/kg (criterium 15.5% ± 4.1% v hilly 3.8% ± 1.7% v flat 3.5% ± 1.4%) and SD in power output (criterium 250 v hilly 165 v flat 169 W). Approximately 67%, 80%, and 85% of total race time was spent below 5 W/kg for criterium, hilly and flat races, respectively. About 70, 40, and 20 sprints above maximum aerobic-power output occurred during criterium, hilly, and flat races, respectively, with most sprints being 6 to 10 s. Conclusions: These data extend previous research documenting the demands of men's road cycling. Despite the relatively low mean power output, races were characterized by multiple high-intensity surges above maximum aerobic-power output. These data can be used to develop sport-specific interval-training programs that replicate the demands of competition.